Virtual Reality Reward Training for Anhedonia: A Pilot Study - Chen, Kelly; Barnes-Horowitz, Nora; Treanor, Michael; Sun, Michael; Young, Katherine S.; Craske, Michelle G. (Frontiers in Psychology, 2021)
Anhedonia is a risk factor for suicide and poor treatment response in depressed individuals. Most evidence-based psychological therapies target symptoms of heightened negative affect (e.g. negative inferential style) instead of deficits in positive affect (e.g. attenuated reward response) and typically show little benefit for anhedonia. Viewing positive scenes through virtual reality (VR) has been shown to increase positive affect and holds great promise for addressing anhedonic symptoms. In this pilot study, six participants with clinically significant depression completed 13 sessions of exposure to positive scenes in a controlled VR environment. Significant decreases were found in self-reported anhedonia, depression, anxiety, and impairments in functioning from baseline to one-month follow-up. Session-to-session decreases were observed for negative affect, but not for positive affect. Results suggest that positive experiences in VR may be a novel avenue for the treatment of anhedonia in depressed individuals.